OPTIMALISASI POSISI JANIN MELALUI PRENATAL YOGA TERHADAP OUTPUT PERSALINAN DI PUSKESMAS WILAYAH KOTA CIREBON - Nurasih, Nurasih; Nurrochmi, Endang (Care : Jurnal Ilmiah Ilmu Kesehatan, 2020)
In Indonesia, Yoga is currently one of the most popular sports, not only for the general public but also for pregnant women. Many benefits can be obtained from prenatal yoga including the mother feeling comfortable and relaxed throughout pregnancy and during childbirth, training the pelvic floor muscles and perineum, keeping the body's muscles relaxed, balanced during childbirth, reducing stress, increasing and improving oxygen circulation to the body and fetus. . This study aims to determine the effect of prenatal yoga on optimizing fetal position on third trimester Primigravida maternal delivery output at Puskesmas Cirebon City. This research is a quasi-experimental research pre post control group design and only post control group design with T test and Chi Square test. Paired T Test results of the intervention group (mean difference = 3.111, P value = 0.000, control group (mean difference = 0.833, P value = 0.318). Independent T Test results obtained (average difference = -1.944, P value = 0.024), Chi Square test obtained a value of P = 0.73. There is a difference in the average anxiety before and after the intervention in the intervention group, there is no difference in average anxiety before and after the intervention in the control group. There is a difference in the average anxiety between the intervention and control groups. There is a difference in mean Long I stage between the intervention and control groups There was no effect of prenatal yoga on the type of labor.